Dupuytren's contracture in Ethiopia. (January 2017) - Gebereegziabher, A.; Baraki, A.; Kebede, Y.; Mohammed, I.; Finsen, V.
Dupuytren's contracture is believed to be rare in Africa. We have observed the disease in many patients coming to our hospital. This study aimed to provide information concerning the occurrence of the disease and risk factors in these patients. All 75 patients who were referred to the hospital during a 2-year period because of a hand problem that was diagnosed as Dupuytren's contracture were included. The demographic data of the patients and possible risk factors were recorded and compared with a control group. The male to female ratio was 18:1. The little and ring fingers were most commonly affected. A total of 43 had bilateral hand involvement. The condition affected only the left hand in one patient. Six men also had fibromatosis of the soles of the feet and three of the penis. There was a statistically significant association with hypertension and alcohol consumption, but not with diabetes mellitus. We conclude that there are more cases of Dupuytren's contracture in Ethiopia than previously thought. Level of evidence: III